Amplitude method of tonal and resonant sounds determination within a speech signal - Hryshchuk, T. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The method of determination of tonal and resonant sections within a signal, which has quasi-periodical regions is suggested in the paper. This information can be used for the speech recognition process efficiency incensement. The idea of quasiperiod and distance between quasiperiods are given. Recommendations for selection of experimental parameters are given in the paper.